Key Management Model Of Added Value In The Historical Tourist Attractions: The Case Studies The Emerald Buddha Temple Bangkok Thailand - Kerdpitak, Chayanan (Journal of Applied Business Research, 2018)
The promotion of the historical tourist attractions is an important mission that should be accomplished to ensure that the tourists have admired ancient sites that are valuable, rare, Inimitable and non – substitution. The tourists are thus enthusiastic to visit the ancient sites and willing to promote and encourage other tourists to visit these tourist attractions. By this reason, the objective of this research is to study the main factors affecting the added value of the tourist to the historical tourist attractions in Thailand. The factors include, Participation Management, Processes Management, Resource Management, Tourists Satisfaction, Tourist Attractions Differentiation and Added Value of Tourists. In this study, the researcher has applied both quantitative and qualitative research methodologies using questionnaires and in-depth interview. The sample comprises visitors to the Temple of the Emerald Buddha. Meanwhile, the path analysis has been used to analyze the data. At the same time the researcher intends to propose the conceptual framework for this study with an aim to identify of the research question, there are any factors affecting to the added value of the visitors to the ancient sites. Moreover, the researcher has recommended 7 assumptions to find out the factors that have effects on the added value of the visitors to the ancient sites. The result has shown that the Tourists satisfaction and the differentiation in tourist attractions have affected the visitors’ added value with the significance level at 0.008. The result of this study can be used to set up the business operations policy of the Thai tourism business. The policy focuses on differentiation placing the development of tourist attractions as first priority followed by the environmental management, the promotion of tourist attractions and the renovation of ancient sites respectively.